Kontribusi Pendidikan Agama Islam Dalam Membentuk Karakter Entrepreneur Mahasiswa Di Era Society 5.0 - Gusmirawati Gusmirawati (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The purpose of this study is to clarify how Islamic education maintains a crucial role in developing individual characters, including those of mahasiswa in the era known as Society 5.0, which is defined by the integration of technology and human life. This qualitative research method uses a literature review and content analysis. Information obtained from literary analysis about the concepts of Islamic education, entrepreneurial traits, and Society 5.0. The analysis's conclusions show that, in the Society 5.0 era, Islamic education can significantly contribute to the development of mahasiswa entrepreneurs. Islam education imparts values, morals, and spiritual teachings that are essential for developing a successful business. The lessons such as jujuran, keadilan, tanggung jawab, and discipline that are taught to students can give them a strong foundation to become ethical and disciplined business owners. Through Islamic education, a strong entrepreneurial character can encourage students to face challenges and opportunities with a bijak, innovative, and forward-thinking mindset in the era of Society 5.0, where technology and humanity are increasingly becoming more integrated. This research provides valuable insights for educational institutions, particularly regarding how to create curricula that align Islamic teachings with the needs of developing female entrepreneurs in the context of Society 5.0. In summary, Islamic education has a strategic advantage in developing students into capable entrepreneurs who can make a positive contribution to society.